2021
DOI: 10.1080/13880209.2021.1953540
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-β-cyclodextrin suppresses the monocyte-endothelial adhesion triggered by lipopolysaccharide (LPS) or oxidized low-density lipoprotein (oxLDL)

Abstract: Chen (2021) Methyl-β-cyclodextrin suppresses the monocyte-endothelial adhesion triggered by lipopolysaccharide (LPS) or oxidized low-density lipoprotein (oxLDL),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…also indicated that Vγ4 + γδ T cells secreted IL-17A via regulating the PI3K/Akt/mTOR axis [ 60 ]. As was reported, LCD strongly modified NF-κB or the mTOR signaling pathway in different cell environments, including monocyte-endothelial adhesion [ 61 ], breast cancer cells’ resistance to TRAIL [ 62 ] and lipid raft-dependent activation in bronchial epithelial cells [ 63 ]. Hence, we inferred that LCD nanoparticles probably influence IL-17A secretion via signaling pathways mentioned above in Vγ4 + γδ T cells, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…also indicated that Vγ4 + γδ T cells secreted IL-17A via regulating the PI3K/Akt/mTOR axis [ 60 ]. As was reported, LCD strongly modified NF-κB or the mTOR signaling pathway in different cell environments, including monocyte-endothelial adhesion [ 61 ], breast cancer cells’ resistance to TRAIL [ 62 ] and lipid raft-dependent activation in bronchial epithelial cells [ 63 ]. Hence, we inferred that LCD nanoparticles probably influence IL-17A secretion via signaling pathways mentioned above in Vγ4 + γδ T cells, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 91%
“…This shows that with an oxLDL target these agents were not acting primarily by disrupting the oxLDL through their action as cholesterol solvents, because the results were very similar with both targets. Previously, MCD had also been shown to cause endothelial cells to reduce adhesion molecule expression and the adhesion of monocytes [ 58 ], and to inhibit monocyte adhesion to endothelial cells stimulated with LPS or oxLDL [ 59 ], although the involvement of lipid rafts in these events was not investigated. In addition, the sensitive disruption shown here of adhesion to FN, which binds primarily to α 5 β 1 integrin, confirms that raft structure is required for integrin mediated adhesion, as determined previously [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on pancreatic and glioma cancer cells showed that methyl-β-Cyclodextrin depletes cholesterol in cell membranes and destroy lipid rafts, leading to an increase in CD44 extracellular lipid distribution, and promoting CD44 related tumor metastasis mediated by ADAM-10, a metalloproteinase ( 72 ). methyl-β-Cyclodextrin can also inhibit cell growth and cell cycle arrest through the expression of cyclin A and D1 mediated by prostaglandin E ( 2 ) independent pathway ( 134 ), and inhibit endothelial adhesion of monocytes induced by lipopolysaccharide or oxidized low-density lipoprotein ( 135 ). The above indicates methyl β-Cyclodextrin may become a new drug for tumor therapy.…”
Section: Potential Role Of Lipid Metabolism Related Drugs In Tumorsmentioning
confidence: 99%